Analisis Citraan dalam Antologi Puisi Titip Pesan pada Tuhan Karya Lenggok Media Production Rokan Hulu - Impon Badri; Misra Nofrita; Hermawan hermawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to describe the imagery contained in the anthology of the poem Titip Message to God by Lenggok Media Production Rokan Hulu. This research method is a qualitative descriptive method. The results of this study were to find 179 images in the anthology of the poem Titip Message Pada God with Lenggok Media Production Rokan Hulu, namely 80 visual images, 45 auditory images, 15 olfactory images, 6 tasting images, 17 tactile images, and 16 motion images. In conclusion, in this poetry anthology visual imagery is more dominant because poetry is more poetry than dark poetry, so that poetry words tend to use denotative language to describe the objects they see and most of the poets adhere to naturalism by describing what is according to their vision. Keywords: Imagery, Leggok, Poetry